If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 2x + -5 = 5x + 3 Reorder the terms: 2 + -5 + 2x = 5x + 3 Combine like terms: 2 + -5 = -3 -3 + 2x = 5x + 3 Reorder the terms: -3 + 2x = 3 + 5x Solving -3 + 2x = 3 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -3 + 2x + -5x = 3 + 5x + -5x Combine like terms: 2x + -5x = -3x -3 + -3x = 3 + 5x + -5x Combine like terms: 5x + -5x = 0 -3 + -3x = 3 + 0 -3 + -3x = 3 Add '3' to each side of the equation. -3 + 3 + -3x = 3 + 3 Combine like terms: -3 + 3 = 0 0 + -3x = 3 + 3 -3x = 3 + 3 Combine like terms: 3 + 3 = 6 -3x = 6 Divide each side by '-3'. x = -2 Simplifying x = -2
| x+7+3x-1+2x+5=0 | | 5-y=-2x-5 | | X=32+2x | | 4x*1=0 | | -q=8+q | | 23x^2+50x+25=0 | | 2x+(x+1)=4 | | m^3+4=1 | | 2x+x+1=4 | | 0.2f=-8.4 | | -12(2-t)=14t | | 4v+10+v-9= | | x+6(4)=29 | | (2d-7)=(2+4d)2 | | a+.75a=21 | | 0=2x^2+1x-6 | | 3x+17+3+7x=x | | 2(-6y+29)-4y=-6 | | (2(23)+21)= | | y,5-6=8 | | 3+n^3=6 | | 90+x+(2x+21)=180 | | 5u-37=2(u+1) | | 90+x+(2x+21)= | | 2+y+3=0 | | -1-8b=-8-9b | | -3y+(6*2)=-6 | | 9y+27=-3x | | -2=-6x+4 | | 8=x-2/7 | | -2p+3=-12 | | 2y+(4*2)=12 |